To Kill A Mockingbird - Lee, Harper; Harper Lee Author (London Penguin Random House, 1960)
To Kill a Mockingbird by Harper Lee centres on Atticus Finch's attempts to prove the innocence of Tom Robinson, a black man who has been wrongly accused of raping a white woman in 1930s Alabama.
Keywords: Fiction -- Southern States-Fiction -- Race Relations-Fiction -- Fathers and Daughters Relation